Efektivitas Pembelajaran Active Learning dengan Metode MIKiR untuk Meningkatkan Keterampilan Kolaborasi Siswa - Yuyun Elfrida Br Simanjuntak; Roma Doni Azmi; Aang Yudho Prastowo (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This research aims to determine the effectiveness of the active learning learning model using the MIKiR method in improving collaboration skills and to find out how much students' collaboration skills have increased in mathematics learning in class VII of SMP Negeri 1 Bintan. The method used in this research is a quasi-experiment type experiment. The research instruments used were a collaboration skills questionnaire and observation sheet. The collaboration skills questionnaire contained aspects of commitment, respect for others, deliberation and participation. Data collection techniques with the experimental class which will receive treatment using active learning learning with the MIKiR method and the control class which will use conventional learning. The data analysis technique uses a non-parametric statistical test, namely the Wilcoxon test. Next, to test the increase, an n-gain test was carried out. The results of this research show that active learning using the MIKiR method is effective in improving students' collaboration skills with a greater average N-gain value for the experimental class, namely 0.48 and an average N-gain for the control class, namely 0.11.